CENTRAL AND EASTERN EUROPE IN THE LIGHT OF THE SPATIAL DISTRIBUTION OF LUXURY STORES – SOME PROBLEMS - Stefania Środa-Murawska; Daniela Szymańska (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2015)
This study analyses the characteristics and structure of luxury goods stores in Central and Eastern Europe (CEE). Studies dealing with the spatial distribution of services created for the super-rich people are relatively few. The authors of this article show luxury goods stores in CEE countries with respect to their locations (urban/rural), location factors, numbers, structure, and the differences between countries and regions. They also consider whether Central and Eastern Europe has space for luxury store networks to expand. The status and structure of luxury goods stores in CEE countries are analysed and evaluated based on secondary data on the authorised retailers of luxury goods. Using the k-mean method as one of its tools, the study shows that luxury goods are mainly offered in large cities (populated by more than 200,000 people). Moscow has been found to have the most extensive network of luxury stores, which gives her a special position among CEE cities. Sankt Petersburg, Prague, Kiev and other European cities with significantly smaller numbers of luxury stores rank lower.